The Influence of Quality on eWOM: A Digital Transformation in Hotel Management - Sánchez-González, Gloria; González-Fernández, Ana M. (Frontiers in Psychology, 2021)
There is no doubt that the use of Internet for purchasing products and services has constituted a crucial change in how people go about buying them. In the era of digital transformation, the possibility of accessing information provided by other users about their personal experiences has taken on more weight in the selection and buying processes. In this sense, traditional word-of-mouth (WOM) has given way to electronic word-of-mouth (eWOM), which in turn has constitute a major social change. This behavior is particularly relevant in the services area, where potential users cannot assess such a service in advance. There is abundant literature analyzing the effects of eWOM on different variables of interest in this sector. However, little is known about the factors that determine the eWOM. Therefore, the main objective of the present paper is to analyze the impact of two variables (objective quality and perceived quality) on such eWOM. Both of them are crucial for potential customers during the process of finding hotel accommodations and they can motivate people to make such comments. The results demonstrate that these variables truly have a significant impact on whether or not users make comments on-line. Moreover, it proved possible to observe certain differences according to the profile of the tourist involved and the destination where the hotel is located. In the current changing environment, this information is of great use for hotel managers in order to design strategies according to the type of guest they wish to attract.